RETHINKING FINANCIAL DEEPENING: FINANCIAL DEVELOPMENT AND GROWTH IN WESTERN BALKANS COUNTRIES WITH REFERENCE TO THE LEVELS OF ECONOMIC DEVELOPMENT AND EURO-INTEGRATION STATUS (The South East European Journal of Economics and Business, 2025)
This article provides an empirical analysis of the relationship between financial development and economic growth, using a sample of nine countries in the Western Balkans from 1995–2022. The study addresses the gap in the literature on financial deepening in the region, specifically regarding its impact on economic development and the Euro-integration status. A novel approach is used to construct the Financial Development Index employing principal component analysis, utilizing a comprehensive matrix of financial proxies for both financial institutions and markets, not previously used in the literature. Results of the dynamic generalised method of moments estimation confirm a significant positive impact of financial deepening on economic growth and income per capita. The positive quadratic term of financial deepening suggests that financial development fosters economic growth. Furthermore, European member states have not yet reached a level of financial development, where the effects of “too much finance” would appear, implying that European integration has not deepened financial development.